EFEK SENYAWA FLAVONOIDS DARI KEMUNING (Murraya paniculata [L.] Jack.) TERHADAP PELEPASAN HISTAMIN DARI KULTUR SEL MAST - Agung Endro Nugroho; Sugeng Riyanto; Mohamad Aspollah Sukari; Kazutaka Maeyama (Majalah Obat Tradisional, 2010)
Murraya paniculata [L.] Jack. (Kemuning) is a plant that grows widely in some areas of Indonesia. Studies related to this plant have been widely explored especially isolation of its active compounds. The plant contents several active compounds such as flanovoids. In the study, three flavonoid isolated from M. paniculata were evaluated for their effect on histamine release from mast cells (RBL-2H3 cells). These compounds were 3,3’,4’,5,5’,6,7,8-octamethoxyflavone; 3,3’,4’,5,5’,6,7-heptamethoxyflavone and 3, 3’, 4’, 5, 5’, 7–hexamethoxyflavone. The histamine inducers used in the study were DNP24-BSA dan thapsigargin, inducing the histamine release immunologically and non-immunologically, respectively. In the study, heptamethoxyflavone and hexamethoxyflavone did not influence the histamine release from mast cells significantly. However, octamethoxyflavone could increase the histamine release from RBL-2H3 cells in absence and presence the histamine inducers. The flavanoid could increase the release of histamine up to 50 %. Based on the results, polymethoxy moieties at the structure of flavonoid have a significant role to emerge the histamine-release stimulating effect from mast cells.